Effect of Dietary Modified-Banana-Tuber Meal Substituting Dietary Corn on Growth Performance, Carcass Trait and Dietary-Nutrients Digestibility of Coloured-Feather Hybrid Duck - Osfar Sjofjan; Danung Nur Adli; Muhammad Halim Natsir; Yuli Frita Nuningtyas; Tika Septi Wardani; Ilmi Sholichatunnisa; Siti Nur Ulpah; Obbi Firmansyah (Indonesian Center for Animal Research and Development (ICARD), 2021)
In this experiment, we investigate the effect of modified banana tuber meal (M-BTM) to substitute dietary maize in growing-finisher colored-feathered hybrid duck. One hundred and ninety six hybrid ducks (Pekin x Khaki Campbell) with 421.31 ± 0.183g body weight (BW) were allotted to 5 dietary treatments with 9 ducks (unsexed) per pen and 4 replications per treatment. These dietary treatments were: NC (negative control; maize-soyabean-meal based diet), BTM25 (25% maize was replaced by M-BTM-), BTM50 (50% maize was replaced by M-BTM), BTM75 (75% maize was replaced by M-BTM), and BTM100 (100% maize was replaced by M-BTM). The experimental design applied using completely randomize design (CRD). Data of this experiment were statistically analysed by one-way-analysis-of-variance of SAS University version 4.0 red hat (64-bit) University Online Edition. Result demonstrated that M-BTM improved significantly (p< 0.05) digestibility of dry matter and crude protein. It is concluded that M-BTM enhanced apparently growth performaces and digestibility parameters of colored-feathered hybrid duck (Pekin x Khaki Campbell).